РЕГІОНАЛЬНА ДИФЕРЕНЦІАЦІЯ ЯК КОНФЛІКТОГЕННИЙ ЧИННИК УКРАЇНСЬКОГО СОЦІУМУ (Zaporizhzhia Historical Review, 2021)
The article deals with regional differentiation of the Ukrainian population during election campaigns in the past years. The author proves, that regionalism of ethnic Ukrainians is based not only upon the ethno-cultural distribution by the axis “east-west”, but also upon substantial differences in political and ideological orientations of these equal-sized parts of the Ukrainian population.